SHEEP DICTYOCAULOSIS AND ITS CONTROL MEASURES - Sharipovna, Sharipova Laylo; Ergashevich, Yo‘ldashev Nurbek (Research Focus International Scientific Journal, 2026)
This article analyzes the prevalence of dictyocaulosis in sheep, its epizootic characteristics, and the effectiveness of control measures against the disease. According to the literature, the disease is widely distributed worldwide, with infection rates ranging from 18.7% to 75.5%, while in the Republic it has previously been reported to reach up to 65.5%. At the same time, the current epizootic status of the disease, patterns of its distribution across different regions, as well as the efficacy of anthelmintic drugs and the level of resistance, remain insufficiently studied. Under conditions of climate change and the intensification of livestock production, this problem is becoming increasingly relevant. Consequently, the need to develop environmentally safe, economically efficient, and scientifically grounded treatment and preventive measures against dictyocaulosis is substantiated.